Effect of vaginal cleansing with povidone iodine prior to emergency caesarean section on post-operative infectious morbidity in a Nigerian tertiary hospital - Ketare, Nathaniel; Abdullahi, Habiba I.; Ayogu, Malachy E.; Ahmed, Rabiat M.; Lawal, Ishak K.; Isah, Dennis A.; Adewole, Nathaniel D.; Isah, Aliyu Y.; Ekele, Bissallah A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Post-caesarean infectious morbidities, including endometritis and wound infections, remain significant contributors to maternal morbidity, particularly in low-resource settings. This study evaluated the effectiveness of preoperative vaginal cleansing with 10% povidone iodine in reducing post-operative infections following emergency caesarean section. Methods: We conducted a randomized controlled trial involving 266 pregnant women booked for emergency caesarean section randomly assigned to either intervention group with povidone iodine vaginal cleansing (n=133) or control group with no vaginal preparation (n=133). Routine prophylactic antibiotics were administered to all participants. The primary outcome was the incidence of post-caesarean endometritis and the secondary outcome was surgical site infection. Results: Of the 266 participants enrolled, only 260 were analysed, 37 (14.2%) of whom developed infectious morbidity. Twenty-nine (22.1%) had infectious morbidity in the control group and 8 (6.2%) in the intervention group. Endometritis occurred in 18 (13.7%) of the control and 4 (3.1%) in the intervention group (p=0.01). Wound infection occurred in 11 (8.4%) of the control and 4 (3.1%) in the intervention group (p=0.07). Vaginal cleansing significantly reduced the risk of endometritis [Risk ratios (RR)=0.21, absolute risk reduction (ARR)=0.11; number needed to treat (NNT=9)] and wound infection (RR=0.38, ARR=0.05; NNT=20), with no reported adverse effects. Conclusions: Preoperative vaginal cleansing with 10% povidone iodine significantly reduced the incidence of post-caesarean endometritis and wound infection. It is a simple, safe, and cost-effective intervention that can improve maternal outcomes, especially in women with prolonged labour or ruptured membranes.